Kadar Flafonoid Bawang Merah Kombinasi Minyak Kayu Putih Sebagi Upaya Penangan Demam Pada Balita - Antari, Gladeva Yugi; Fatmawati, Nurul (STIKES Yarsi Mataram, 2024)
Based on data (WHO) there are 17 million cases of fever in toddlers, of which 500-600 thousand cause death. The number of fever cases in Indonesian toddlers is estimated to be between 800-100,000 toddlers each year. Fever cases in NTB Province in 2021 decreased compared to the previous year. In 2020 there were 3,919 cases, decreasing 0.69 times to 2,719 cases in 2021 with 18 deaths. Fever is a condition where the body temperature is above normal, namely >38°C. Traditional treatment for fever can be done by giving onion compresses. One of the phytochemical compounds found in shallots is flavonoids. The method in this study was to conduct laboratory tests on shallots combined with eucalyptus oil at the Food Chemistry and Biochemistry Laboratory, Faculty of Food Technology and Agroindustry, University of Mataram on January 17, 2024. The results of this study showed that the total flavonoid content of shallots combined with eucalyptus oil was 28.05%.